PENGUATAN PUBLIKASI KARYA ILMIAH BAGI GURU MADRASAH TSANAWIYAH NEGERI 6 SRAGEN - Abbas, Ngatmin; Setiawan, Andi; Agustin, Riska; Fani Rahma, Sari (UNIVERSITAS SERAMBI MEKKAH, 2024)
This community service aimed to enhance the ability of teachers at Madrasah Tsanawiyah Negeri 6 Sragen in writing and publishing scientific works. The method used was a workshop combining theory and practice, covering the importance of publication, scientific writing techniques, and the process of submitting to academic journals. The results showed a significant improvement in participants' understanding and skills, with 61.8% stating they fully understood the importance of scientific publication and 70.6% rating the workshop material as highly effective. 73.5% of participants felt greatly assisted in understanding the publication submission process. The implications of this activity include the potential increase in the quantity and quality of scientific publications from madrasah teachers, which can contribute to the development of Islamic education and enhance the institution's academic reputation. However, 44.1% of participants still require further practice, indicating the need for ongoing mentoring programs. This activity successfully catalyzed the building of an academic culture within the madrasah environment and strengthened the scientific tradition in Islamic education.